Sustainability of the seaweed Hypnea pseudomusciformis farming in the tropical Southwestern Atlantic - Pereira, Stefany A. [UNESP]; Kimpara, Janaina M.; Valenti, Wagner C. [UNESP] (Elsevier B.V., 2021)
Seaweed culture is generally referred to as a sustainable production system. Nevertheless, this concept is biased by an environmental approach only, neglecting the economic and social dimensions of sustainability. The objective of this study was to assess the sustainability of the seaweed Hypnea pseudomusciformis cultivation and its use as human food consumption. We developed a pilot farming with the Association of Algae Producers of Flecheiras and Guajiru, in the municipality of Trani, Northeastern Brazil. We applied a set of indicators to access environmental, social, and economic dimensions of sustainability. The environmental indicators showed highly efficient use of energy, nitrogen and phosphorus, which increased in the algae biomass during culture by 383%, 894%, and 1860%, respectively. Besides, H. pseudomusciformis culture absorbs carbon, does not pollute, and shows low risk to the local biodiversity because of it is a native species. Social indicators revealed that 51% of all investment stays in the local community, and the income distribution is equal among workers. The farm presented a high labor demand, which is socially inclusive. The H. pseudomusciformis farm was highly profitable, with an internal rate of return of 119%, recovery of invested capital in 1.2 years and positive externalities, generating 262.00 US$.t(-1) as additional income. The farm showed high performance in the environmental, economic, and social dimensions of sustainability. Thus, this activity may be a sustainable manner to produce high-quality human food and raw materials for industry. The results obtained in the present study provide secure information for farmers, investors, and policymakers, which may encourage small and medium farmers to start seaweed farming in tropical Atlantic Southwestern coast.
Keywords: Macroalgae; Ecosystem services; Sustainability; Bioeconomy; Externalities; Socio-economic